Drought Index Determination Using the Batulayar Watershed Hydrology Model - Sri Rahayu Ayuba; Wilan Mooduto; Risman Jaya; Tisen Tisen; Ahmad Syamsurijal; Munajat Nursaputra (Journal La Lifesci, 2022)
The Batulayar sub-watershed, also known as the Bongomeme sub-watershed, is one of the most important sub-watersheds in the Limboto watershed. Because there are oil palm and other plants in the Batulayar Sub-upstream watershed's area that cause drought and natural harm. The goal of this study was to assess the severity of the drought and develop a hydrological model for calculating the drought index in the Batulayar sub-upstream watershed's area. The mix approach was utilized, which combines Soil and Water Assessment Tool (SWAT) modeling with field survey methodologies. The study's findings suggest that land conversion in the Batulayar Sub-upstream watershed's area may have an impact on the watershed's function. The Batulayar Sub-SMDI watershed's value in the SWAT Model results shows that it ranges from -0.50 to -2.99 in March, April, May, November, and December over a 10-year period, and is classified as "Slightly Dry" and "Slightly Dry." The Hydrological Model's role in determining the drought index can be seen in the results of calibration and validation using the NSE Model (Nash Sutcliffe Coeficient of Efficiency). An NSE value of 0.9 is obtained in calibration and validation, implying that the NSE value obtained belongs to the "good" class or that the discharge model and research observation discharge are similar.